Formation of a New Mission of Higher School in the Transforming World Innovation Space. The Economics of Science - О. B. Voeykova (Ekonomika Nauki)
The article purpose was to determine the place of modern higher education in the structure of the global innovative space, considering the preservation of itself as a national identification center, which required understanding and formalization of its new mission for conditions of high geo-economic instability caused by the processes of deglobalization in the world economy.As a research methodology, the work uses a nonlinear method synthesizing systemic and evolutionary approaches. This allows, on the one hand, to determine the place of higher education in the structure of the global innovation space. On the other hand, to reflect the qualitative, evolutionary transformations taking place in it against the background of increasing destabilization within this broader system, respectively, to show the evolution the missions of the higher school under the influence of the changes that have arisen.An important result of the research was the definition of a new mission of the higher school, which consists not only in its acquisition of subjectivity in the creation and promotion of innovations at the global level, but also in its formation as a sovereign (independent) center of national identity with a certain share of its own supranational influence on the world innovation space, including in terms of eliminating the global innovation separation.